Islamic Republic of Afghanistan : Interim Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
This paper provides an initial comprehensive framework for Afghanistan to build institutions, sustain growth, and reduce poverty. First, macroeconomic, political, and security risks were identified. As the interim strategy presents a very ambitious five-year framework, there is an urgent need for prioritization. The lack of human resources is the major constraint. The investments proposed for agriculture and rural development show a strong commitment to rural areas and to supporting the private sector. The government needs a realistic timeline to complete the Afghanistan National Development Strategy.